Cold case files : palaeoforensic and taphonomic study of the Mamafura dicynodont from the end permian - Fordyce, Nicholas (Department of Biological Sciences, 2017)
Dicynodonts were non-mammalian herbivorous therapsids (mammal-like reptiles) that flourished world-wide during the Permian and Triassic Periods. They are nowhere more abundant than in the rock strata of the Karoo basin in South Afiica. Taphonomy, the transition from biosphere to lithosphere, is of great geological and biological significance and has provided remarkable insight into palaeoenvironments. A partially articulated dicynodont that has been fossilised alongside an unidentified predator tooth shows evidence of predation and is analysed here. The dicynodont is possibly Oudenodon grandis and was most likely drowned after which it was scavenged from by a gorgonopsian predator, Aelurognathus. The fossil is important as it provides further insight into the ecology of the Late Permian and it enhances our taphonomic understanding.